Processing speed and memory test performance are associated with different brain region volumes in Veterans and others with progressive multiple sclerosis - Spain, Rebecca I.; Hildebrand, Andrea; Waslo, Carin S.; Rooney, William D.; Emmons, Joshua; Schwartz, Daniel L.; Freedman, Mark S.; Paz Soldan, M. Mateo; Repovic, Pavle; Solomon, Andrew J.; Rinker, John; Wallin, Mitchell; et al. (Frontiers in Neurology, 2023)
Background Cognitive dysfunction and brain atrophy are both common in progressive multiple sclerosis (MS) but are seldom examined comprehensively in clinical trials. Antioxidant treatment may affect the neurodegeneration characteristic of progressive MS and slow its symptomatic and radiographic correlates. Objectives This study aims to evaluate cross-sectional associations between cognitive battery components of the Brief International Cognitive Assessment for Multiple Sclerosis with whole and segmented brain volumes and to determine if associations differ between secondary progressive (SPMS) and primary progressive (PPMS) MS subtypes. Design The study was based on a baseline analysis from a multi-site randomized controlled trial of the antioxidant lipoic acid in veterans and other people with progressive MS (NCT03161028). Methods Cognitive batteries were conducted by trained research personnel. MRIs were processed at a central processing site for maximum harmonization. Semi-partial Pearson's adjustments evaluated associations between cognitive tests and MRI volumes. Regression analyses evaluated differences in association patterns between SPMS and PPMS cohorts. Results Of the 114 participants, 70% had SPMS. Veterans with MS made up 26% (n = 30) of the total sample and 73% had SPMS. Participants had a mean age of 59.2 and sd 8.5 years, and 54% of them were women, had a disease duration of 22.4 (sd 11.3) years, and had a median Expanded Disability Status Scale of 6.0 (with an interquartile range of 4.0–6.0, moderate disability). The Symbol Digit Modalities Test (processing speed) correlated with whole brain volume (R = 0.29, p = 0.01) and total white matter volume (R = 0.33, p < 0.01). Both the California Verbal Learning Test (verbal memory) and Brief Visuospatial Memory Test-Revised (visual memory) correlated with mean cortical thickness (R = 0.27, p = 0.02 and R = 0.35, p < 0.01, respectively). Correlation patterns were similar in subgroup analyses. Conclusion Brain volumes showed differing patterns of correlation across cognitive tasks in progressive MS. Similar results between SPMS and PPMS cohorts suggest combining progressive MS subtypes in studies involving cognition and brain atrophy in these populations. Longitudinal assessment will determine the therapeutic effects of lipoic acid on cognitive tasks, brain atrophy, and their associations.